2023
DOI: 10.3390/app13074320
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Potential of Four Novel Halotolerant Bacterial Strains as Plant-Growth-Promoting Rhizobacteria (PGPR) under Saline Conditions

Abstract: Soil salinity, due to natural phenomena or human activities, alters the water potential, which in turn affects plant growth, negatively influencing their nutrient and water uptake. Plant-growth-promoting rhizobacteria (PGPR) can be used to counteract these negative effects, especially in glycophytes. The aim of our study was to characterize physiologically, genetically, and biochemically the novel halotolerant/halophilic bacteria isolated in our previous work. We evaluated the plant-growth-promoting (PGP) feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
0
0
Order By: Relevance
“…Recently, most research has focused on the isolation and study of halotolerant and halophilic bacteria with plant growth potential [53][54][55]. In our work, all the isolated bacteria could fix molecular nitrogen and solubilize mineral phosphate.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Recently, most research has focused on the isolation and study of halotolerant and halophilic bacteria with plant growth potential [53][54][55]. In our work, all the isolated bacteria could fix molecular nitrogen and solubilize mineral phosphate.…”
Section: Discussionmentioning
confidence: 94%
“…IAA-producing microorganisms stimulate root growth, allowing for increased nutrient and water use efficiency [57][58][59][60]. The simultaneous expression of different PGP traits promotes plant growth [53] and increases the potential of the isolates to be used as plant biostimulants, especially under stress conditions such as saline soils.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 includes other Halomonas strains that have been reported. Some Halomonas species isolated from plants have been shown to have potential as PGPB [132,133] or in phytoremediation to improve soils [125] (Table 1). A collection of halotolerant microbes isolated from Salicornia ramiosissima [132] contains some isolates with PGPB activity.…”
Section: Salt-tolerant Bacterial Genus Halomonasmentioning
confidence: 99%
“…A collection of halotolerant microbes isolated from Salicornia ramiosissima [132] contains some isolates with PGPB activity. Two Halomonas and two Bacillus strains were identified from the rhizosphere of quinoa that have different activities as PGPB, and it was shown that these strains exhibit beneficial traits that are salt-regulated [133].…”
Section: Salt-tolerant Bacterial Genus Halomonasmentioning
confidence: 99%